Blindsided - Cummings, Priscilla, 1951- (New York : Dutton Children's Books, 2010)
After years of failing eyesight, fourteen-year-old Natalie reluctantly enters a school for the blind, where in spite of her initial resistance she learns the skills that will help her survive in the sighted world.
Keywords: Blind -- Fiction; People with disabilities -- Fiction; Schools -- Fiction; Maryland -- Fiction